A Sociocultural Perspective on English-as-a-Foreign-Language (EFL) Teachers’ Cognitions About Form-Focused Instruction - Sun, Qiang; Zhang, Lawrence Jun (Frontiers in Psychology, 2021)
There has been much research into teacher beliefs about teaching and learning as seen in the general teacher education literature. In the field of language teacher education, this line of research has been evolving, with the recent trend being streamlined into “teacher cognition” as a generic or umbrella term. Despite increasing amounts of research output so far, research into foreign language teachers’ cognitions about their own teaching and decision-making is still insufficient, particularly with regard to university-level English-as-a-foreign-language (EFL) teachers in China. Drawing on Vygotsky’s Sociocultural Theory, this qualitative research focused on EFL teachers’ cognitions about form-focused instruction in Chinese university settings. It intended to discover how teachers’ cognitions changed when they were expected to teach in actual classrooms and what factors contributed to these changes. Data collected from four teacher-participants through semi-structured interviews, classroom observations and follow-up stimulated recall interviews showed participants’ support for focus-on-form instruction, which means they not only paid attention to the grammatical form of the language but also to the meaning it is intended to convey. However, data also showed that the teacher-participants shifted from focus-on-form to focus-on-formS instruction in actual teaching, which suggests that they might have realised the challenges of carrying out teaching activities surrounding focus-on-form and would like to take an easier approach by only teaching the grammar of the language by focusing on formS. Such incongruences are interpreted with reference to a plethora of sociocultural factors including traditional Chinese thinking and institutional expectations. The implications of the findings for stakeholders in universities, including faculty members, students, and curriculum developers in similar contexts, are also discussed.